AESTHETIC THEORY AND REALISM IN ENGLISH LITERATURE. ON THE EXAMPLE OF THE WORKS OF O. YALD (Web of Teachers: Inderscience Research, 2024)
This article examines the significance of aesthetic theory and realism in English literature, focusing on the works of O. Yald. It explores how aesthetic principles enhance artistic beauty while realism grounds literary expression in authentic depictions of life. Through the lens of Yald’s writing, the study highlights the seamless integration of these two frameworks, showcasing his ability to create narratives that are both profoundly beautiful and strikingly realistic. The article emphasizes Yald’s contribution to English literature as a master of blending artistic elegance with truthful representation.